2013
DOI: 10.1074/jbc.m113.503128
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Argininosuccinate Lyase Transcript Variants in the Clinical and Biochemical Variability of the Urea Cycle Disorder Argininosuccinic Aciduria

Abstract: Background:The role of argininosuccinate lyase (ASL) transcripts in disease variability is unclear. Results: The most common ASL transcript variants decrease the functional enzymatic activity after co-expression with wild type or mutant ASL. Conclusion: ASL transcripts expressed at high levels can contribute to the variable phenotype in ASL-deficient patients. Significance: A new explanation of the molecular basis adds to our understanding of the clinical variability in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…We have previously shown that 293 T cells were an ideal ASL expression system lacking endogenous ASL but allowing for high ectopic ASL expression (Hu et al 2013). Cells were grown, maintained and transiently transfected as described before (Hu et al 2013).…”
Section: Expression Of Asl Constructs In Human Embryonic Kidney 293t mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that 293 T cells were an ideal ASL expression system lacking endogenous ASL but allowing for high ectopic ASL expression (Hu et al 2013). Cells were grown, maintained and transiently transfected as described before (Hu et al 2013).…”
Section: Expression Of Asl Constructs In Human Embryonic Kidney 293t mentioning
confidence: 99%
“…Full-length ASL cDNA (1395 bp, RefSeq NM_000048.3) was cloned into the expression vector pcDNA3 (Invitrogen, Carlsbad, CA, USA) at BamHI and NotI restriction sites yielding pcDNA3-ASL-WT (P-WT) as described previously (Hu et al 2013). The mutant plasmids were constructed based on P-WT by site-directed mutagenesis (Phusion Site-directed mutagenesis Kit, Finnzymes, Espoo, Finland) according to manufacturer's protocol.…”
Section: Construction Of Recombinant Asl Mutationsmentioning
confidence: 99%
See 3 more Smart Citations